SOSIALISASI BUDIDAYA RUMPUT GAJAH MINI DI AIR RUNDING KECAMATAN KOTO BALINGKA KABUPATEN PASAMAN BARAT - Ferry Lismanto Syaiful; Rahma Sarita (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Mini elephant grass (Pennisetum purpureum cv. Mott) is a very productive type of grass with a high nutrient content and is highly preferred by ruminants. This grass is small in size, has hairy stems, increased productivity, and has a 10–15% protein content. This grass can live in various places, is resistant to protection, responds to fertilization, and requires fertile soil. This elephant grass has the potential to be given to ruminants, so increased grass production needs to be raised with good cultivation techniques. This activity aims to increase the knowledge and understanding of farmers/breeders in the cultivation of superior grass/mini elephant grass (Pennisetum purpureum cv. Mott). This activity was carried out in the Air Meruding Nagari Air Bangis area, Sungai Beremas District, West Pasaman Regency. This activity was carried out by lecturers and students of the Faculty of Animal Husbandry, Andalas University, and their partners. The target activities (partners) involved in this activity are breeders and the community in the Air Merunding area, West Pasaman Regency. The stages of implementing the training include outreach/counseling, demonstration of planting mini elephant grass, monitoring, and evaluation. The results of the activities obtained from the mini elephant grass planting activities are given, where partners can plant mini elephant grass well. Furthermore, partners also benefit and have learned about growing superior grass as animal feed and gaining knowledge in the application of this grass. By planting excellent grass, partners/breeders are greatly assisted in overcoming difficulties in finding forage for their livestock.